PENGEMBANGAN STRATEGI BELAJAR dan PEMBELAJARAN MENGGUNAKAN MODEL MULTIMEDIA INTERAKTIF (Sebuah Tinjauan) - Dedi Saputra (Jurnal Khatulistiwa Informatika, 2014)
The ability to formulate a plan of action learning and learning as well as the use of methods and utilization of various resources / media in learning aimed at achieving the maximum in an education. This means that in the drafting of a new strategy to the learning process of preparing an action plan to achieve specific goals, learning strategies must be directed to facilitate the achievement of competencies in the curriculum document has been designed so that each individual is able to become independent lifelong learners, and which in their turn an essential component to realize a learning society. The process of teaching and learning can not be separated from the support of a media in this media-based interactive multimedia. Utilization of interactive media is used as a means to deliver material for a teacher to the learner.Keyword: Strategy, Learning and Learning, Interactive Multimedia